(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2018)
The analysis and assessment of the performance of the apartment property was based on a survey of the property management system and a study of the profitability of a typical apartment. The subject of the analysis was an apartment located in the Aquarius aparthotel in Kolobrzeg. The main objective of the study was to determine factors influencing the level of profitability of a typical apartment and assessing its profitability.